Mediators of protection against lethal systemic vesicular stomatitis virus infection in hamsters: defective interfering particles, polyinosinate-polycytidylate, and interferon. - Fultz, P N (1982)
Homologous defective interfering (DI) particles protected adult Syrian hamsters against lethal systemic infection with vesicular stomatitis virus (VSV) serotype Indiana. The DI particles had to be biologically active, but did not have to be administered at the same inoculation site as the infectious virus. Serum and tissue levels of VSV postinoculation were significantly lower in DI-protected animals than in unprotected controls, suggesting that true autointerference was occurring. However, some aspects of protection also must be mediated through nonspecific mechanisms, since susceptible hamsters could be protected against VSV Indiana by coinjection with heterologous DI particles prepared from VSV serotype New Jersey or by simultaneous administration of polyinosinic acid-polycytidylic acid. By measuring serum levels of putative hamster interferon (type 1), we found that animals coinjected with VSV and DI particles or polyinosinic acid-polycytidylic acid produced significant levels of interferon. Since similarly high serum levels of interferon were measured in recipients of VSV alone (animals that eventually died from infection), there appeared to be no correlation between protection against lethal disease and induced levels of serum interferon. Instead, serum interferon levels correlated positively with amounts of VSV PFU found in serum and tissues of infected animals, the lowest levels being found in serum of animals protected with homologous DI particles. The data are consistent with the hypothesis that autointerference by DI particles as well as various host defense mechanisms (possibly including induction of interferon) participates in protecting hamsters against lethal VSV infection.